(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
Venture capital is a type of private equity capital typically provided by professional, outside investors to new, growth businesses. This form of raising capital is popular among new companies, or ventures, with limited operating history, who cannot raise funds through a debt issue. The survey results show that in a relatively short period of time Poland have become dynamic private equity markets. It is expected that the trends seen in the past will only accelerate in the foreseeable future.